IMPLEMENTASI PERAN HUMAS DALAM PUBLIKASI ONLINE DI PLN INDONESIA POWER UBP JABAR 2 PELABUHAN RATU - Juliana, Vania; Darmawan, Leonard (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
This study aims to analyze the implementation of the Public Relations (PR) role in online publication activities at PLN Indonesia Power UBP Jabar 2 Pelabuhan Ratu. The role of PR goes beyond merely disseminating information; it involves managing digital communication strategies to build a positive corporate image. This research adopts the public relations theory of Cutlip and Center (1982), which includes four key stages: Research– Listening, Planning–Decision, Communication–Action, and Evaluation. A descriptive qualitative method was employed, using data collection techniques such as observation, in-depth interviews, documentation, and literature review. The findings show that the PR Division is actively involved throughout the entire digital publication process—from data collection and content planning based on platforms, to the production of visual and narrative materials, and evaluation through the Web Scoring system. Communication is carried out in a two-way manner and tailored to the characteristics of both social media and news portals. Regular evaluation ensures message consistency and effectiveness. This implementation reflects a modern public relations practice that adapts to digital transformation and contributes positively to increasing transparency and public trust in the company.